2010
DOI: 10.1002/mnfr.200900240
|View full text |Cite
|
Sign up to set email alerts
|

Safety assessment of botanicals and botanical preparations used as ingredients in food supplements: Testing an European Food Safety Authority‐tiered approach

Abstract: This article describes results obtained by testing the European Food Safety Authority-tiered guidance approach for safety assessment of botanicals and botanical preparations intended for use in food supplements. Main conclusions emerging are as follows. (i) Botanical ingredients must be identified by their scientific (binomial) name, in most cases down to the subspecies level or lower. (ii) Adequate characterization and description of the botanical parts and preparation methodology used is needed. Safety of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 44 publications
(45 reference statements)
0
28
0
1
Order By: Relevance
“…It is important to note that most of these traditional botanical products have never been the subject of thorough pre-marketing toxicological safety assessment as required, for example, for modern pharmaceuticals or food additives (Schilter et al 2003;Speijers et al 2010). Based on their traditional use for long periods of time, these botanical preparations are often assumed to be safe.…”
mentioning
confidence: 99%
“…It is important to note that most of these traditional botanical products have never been the subject of thorough pre-marketing toxicological safety assessment as required, for example, for modern pharmaceuticals or food additives (Schilter et al 2003;Speijers et al 2010). Based on their traditional use for long periods of time, these botanical preparations are often assumed to be safe.…”
mentioning
confidence: 99%
“…Besides, the Scientific Committee of the European Food Safety Authority (EFSA) stated that it is important to ensure the botanical ingredients used in food supplements are safe to consume and O. tenuiflorum that is possible to cause reproduction toxicity was evaluated. The result of the evaluation showed that there was no information regarding toxic compounds for that effect (Gerrit et al, 2010).…”
Section: Mineral and Heavy Metal Analysismentioning
confidence: 98%
“…Another reason for the restricted use of phytogenic substances as methane inhibitors may be their potential transfer from feed into food of animal origin and possible residues in animal products and their effects in humans (EFSA, 2009;Speijers et al, 2010).…”
Section: Presently No Significance ⇑mentioning
confidence: 99%